PUBLIC SECTOR ACCOUNTING REFORM: A SYSTEMATIC LITERATURE REVIEW - Mariana Mariana; Diana, Diana; Arifai, Muhammad; Jannah, Miftahul (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
This study aims to identify and categorize key findings in the literature related to public sector accounting reform, analyze the challenges and impacts of implementing accrual-based accounting, and formulate research directions and policy recommendations. The method employed is a Systematic Literature Review (SLR) of 10 national and international scholarly articles published between 2018 and 2023. The findings reveal that the implementation of accrual accounting in the public sector faces various challenges, including institutional barriers, bureaucratic resistance, dual reporting burdens, and a lack of digital infrastructure. Nevertheless, this reform also offers potential improvements in transparency, accountability, and efficiency in public financial management. This review recommends strengthening human resource capacity, integrating information systems, a phased transition approach, and harmonizing central and regional policies to support effective and sustainable accrual implementation.